Public perceptions of an avian reintroduction aiming to connect people with nature - Rachel L. White; Lizzie P. Jones; Lucy Groves; Michael A. Hudson; Rosalind J. Kennerley; Sarah L. Crowley (People and Nature, 2023)
Abstract Species reintroductions are an increasingly popular conservation tool, typically aiming to achieve direct conservation benefits. Socio‐cultural drivers also exist but have, to date, received very little attention in research and policy. As a case study, we focus on the recent and ongoing reintroduction of the white stork Ciconia ciconia to England, key drivers of which include connecting people with nature, providing local socio‐economic benefits and inspiring environmental restoration. We surveyed 3531 people in Britain to establish and explore baseline perceptions toward white storks and their reintroduction, including their cultural salience. Findings were compared and evaluated between (i) self‐selecting and nationally representative samples and (ii) residents living close to release sites versus non‐locals. In contrast to self‐selecting participants, most of the nationally representative sample had never heard of nor seen a white stork and were unaware of the reintroduction. Attitudes were more positive in the self‐selecting sample and neutral or uncertain in the nationally representative sample. Consequently, to assess views of both engaged communities and wider publics, we recommend reintroductions adopt a similar two‐mode sampling strategy to that used here when undertaking social feasibility assessments/public consultations. Eighty‐six percent of participants supported the reintroduction overall. Reasons provided for support were diverse, relating to perceived or experienced socio‐cultural benefits and values, general biodiversity enrichment, and moral impetus to restore formerly native species. Criticisms, raised by a minority, related to uncertainty/disagreement about the white stork's formerly native status; rigour of the ecological risk assessment; and a perceived lack of transparency regarding how the project supports conservation efforts. Given that reintroductions have underexplored potential to (re)establish socio‐cultural relationships between people, wildlife and landscapes, and these are increasingly cited as justifications for reintroductions, we encourage further discussion and research in this area. Read the free Plain Language Summary for this article on the Journal blog.